Pengenalan Aplikasi "Khan Academy Kids" Guna Menunjang Pembelajaran Bahasa Inggris dan Penanaman Nilai Baik - Lisa Suhayati; Haryati Haryati; Rahmita Egilistiani; Yuli Wahyuni (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The use of technology during the current pandemic facilitates the process of online teaching and learning activities. One of the digital applications that can support learning English is Khan Academy. Khan Academy offers educational videos and exercises in various contents. The application helps educators and students to meet the educational challenges faced in the current pandemic conditions. The use of Khan Academy has been implemented in many developing countries including Indonesia. The purpose of this Community Service activity is to find out the effect of using the Khan Academy application on learning English and inculcating good values in students. In the activity, the writers focus one to see the development of children character building and increase motivation to learn English. It was held at TBM Sanggar Baca Jendela Dunia Ciputat. The descriptive qualitative was applied to explore the results. It has two aspects of outcomes: using digital applications, children are expected to achieve reinforcement to improve English language skills, and children at Sanggar Baca Jendela Dunia are expected to obtain the positive development of character buildings which are enthusiasm, independence, and thoroughness in the English learning process. The use of this application is expected to have a lot of positive impacts for students to support academic and non- academic achievements, as well as in daily activities.